1999
DOI: 10.1002/(sici)1098-240x(199912)22:6<435::aid-nur2>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation theory and coping with physical illness

Abstract: A self-regulation theory of how patients cope with events that occur during physical illness that has received substantial support from research is described. The theory challenges some traditional thinking about providing patients information and patients' emotional responses to threatening health care events. The use of the theory in practice and suggestions for research to further develop the theory are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
8

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(109 citation statements)
references
References 31 publications
5
96
0
8
Order By: Relevance
“…This can be done effectively in a relatively brief time period preferably using either audiotaped or videotaped information as written pamphlets do not appear to be as effective (Tinsley et al 1988). Past research suggests that this information may be most effective when it is based on experienced patients' perceptions of the therapy (Johnson 1999) and when it includes information on the objective events that could be expected (i.e., what the patient or client will actually do or experience).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done effectively in a relatively brief time period preferably using either audiotaped or videotaped information as written pamphlets do not appear to be as effective (Tinsley et al 1988). Past research suggests that this information may be most effective when it is based on experienced patients' perceptions of the therapy (Johnson 1999) and when it includes information on the objective events that could be expected (i.e., what the patient or client will actually do or experience).…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and colleagues have also demonstrated that these findings generalize to males and females as well as children and adults (Johnson 1999). Moreover, results generalize to patients' ability to cope with medical procedures that last for an extended duration, a situation not unlike psychotherapy.…”
Section: Introductionmentioning
confidence: 86%
“…Strategies to cope with illness risk are taken to attain a desired outcome. Cognitive and emotional processes are used when considering adoption of health behaviors and occur in parallel fashion [50]. Perceptions of perceived risk, perceived seriousness of illness and perceived control influence these decisions [12].…”
Section: Self-regulation Theorymentioning
confidence: 99%
“…The first educational approach that we tested was based on Johnson's Self-Regulation model theory [31,35]. A substantial literature based on Johnson's selfregulation theory has developed, demonstrating that provision of objective concrete information about sensory experiences and about coping tactics can improve a patient's ability to cope with noxious medical experiences.…”
Section: Intervention Development and Testingmentioning
confidence: 99%